Enhancing Elementary Students’ Learning Interest in Pancasila Education through Wordwall Educational Games - Ni Putu Dessy Wiranti; Dewa Bagus Sanjaya; I Nengah Suastika (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aimed to examine the effect of Wordwall educational games on the learning interest of fifth-grade elementary school students in Pancasila Education. This study employed a quantitative approach with a quasi-experimental design using a posttest-only non-equivalent control group design. The population consisted of fifth-grade students in SD Gugus IX Mengwi, Badung. The sample was selected through random sampling, involving 19 students of SD No. 1 Gulingan as the experimental class and 28 students of SD No. 3 Gulingan as the control class. Data were collected using a learning interest questionnaire and analyzed through descriptive statistics, assumption testing, and an independent sample t-test. The results showed that the mean score of the experimental class was higher than that of the control class. The independent sample t-test showed a significance value of 0.000, which was lower than 0.05. This finding indicated that Wordwall educational games had a significant effect on students’ learning interest. Wordwall provided interactive, enjoyable, and game-based learning experiences that encouraged students’ attention and participation in Pancasila Education learning.